Ecological Interactions in Silvopastoral Systems: A Synthesis - Jose, Shibu (Annals of Arid Zone, 2016)
With increasing interest in environmental quality and income diversitication, tree-based systems such as silvopasture are receiving considerable attention as a .new strategy for agroecosystem management. Properly managed silvopasture can provide many environmental benefits such as enhanced water quality and improve small- farm profitability by providing multiple income sources. However, "propcr management" is an ambiguous term, since managing a silvopastoral system involves - managing complex interactions involved among its trce, forage and animal components. Our knowledge about the competitive and complementary interactions that define silvopastoral system productivity and sustainability is rather limited. The objectives of this paper are to review the available literature on the complex interactions in silvopastoral systems around the world and identify research priorities. The limited literature on interactions indicates that research emphasis should be placed on this important topic so that appropriate management techniques can be devcloped.